Write source 2000 : a guide to writing, thinking, & learning - Sebranek, Patrick; Kemper, Dave.; Meyer, Verne (Wilmington, MA : D.C. Heath, 1995)
In handbook format, discusses a variety of principles related to the writing process, such as composition techniques, creative thinking skills, grammar, and proofreading tips.
Includes index.
Young Adult
Keywords: Authorship; Creative writing; English language -- Composition and exercises; English language -- Grammar; Authorship; Creative writing; English language -- Composition and exercises; English language -- Grammar